Selection of marketing channels by intensive horticultural crop growers in Almeria - Martinez-Carrasco Pleite, F.
(Es, En)
ilus., 26 ref.
Keywords: MERCADEO; MODELOS; INVERNADEROS; ESPAÑA; MODELOS LOGIT